The Histopathological Changes in Rat Femur That Were Fed with Low-Calcium Diet in Lactation and Postlactation Periods - KETANI, M.Aydin; NERGIZ, Yusuf; DEVECI, Engin; AKKUS, Murat; SANLI, Ayfer; GUNEY, Berna (Annals of Medical Research, 2021)
None
Keywords: s : Low-calcium diet, femur, lactation, postlactation period, rat